2018
DOI: 10.1587/transinf.2017mup0005
|View full text |Cite
|
Sign up to set email alerts
|

Robust Image Identification without Visible Information for JPEG Images

Abstract: Kenta IIDA† , Student Member and Hitoshi KIYA †a) , Fellow SUMMARY A robust identification scheme for JPEG images is proposed in this paper. The aim is to robustly identify JPEG images that are generated from the same original image, under various compression conditions such as differences in compression ratios and initial quantization matrices. The proposed scheme does not provide any false negative matches in principle. In addition, secure features, which do not have any visual information, are used to achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Note that Recall = 100[%] means that there were no false negative matches, and Precision = 100[%] means that there were no false positive matches. It is confirmed that proposed scheme achieved Recall = 100% for all databases, although the conventional compression-dependent schemes [7], [9] did not. The schemes [7], [9] guarantee Recall = 100% for singlecompressed images in principle, however, it does not consider the errors caused by double-compression.…”
Section: Performance For Images From Ukbenchsupporting
confidence: 57%
See 3 more Smart Citations
“…Note that Recall = 100[%] means that there were no false negative matches, and Precision = 100[%] means that there were no false positive matches. It is confirmed that proposed scheme achieved Recall = 100% for all databases, although the conventional compression-dependent schemes [7], [9] did not. The schemes [7], [9] guarantee Recall = 100% for singlecompressed images in principle, however, it does not consider the errors caused by double-compression.…”
Section: Performance For Images From Ukbenchsupporting
confidence: 57%
“…, the client/user judges that O ′ i and Q ′′ are generated from different original images and the process for image As shown above, by using the feature extracted from DC coefficients, the identification is carried out in the proposed scheme, although the conventional schemes use all DCT coefficients [9]- [11] or the signs of DCT coefficients [7], [8]. The following are the reasons why this feature is used in this paper.…”
Section: ) Identification Processmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, due to the use of robust features against JPEG errors, compression-method-dependent schemes [7]- [13] have the stronger robustness than the first type ones. The schemes [7]- [10] use positive and negative signs of discrete cosine transform (DCT) coefficients, and the schemes [11]- [13] focus on the positions in which DCT coefficients have zero values. However, the identification for images having different sizes can not be performed.…”
Section: Introductionmentioning
confidence: 99%